2017
DOI: 10.1021/acs.jafc.7b03913
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Signs and Subcellular Imaging Provide Insight into the Antifungal Mechanism of Carabrone against Gaeumannomyces graminis var. tritici

Abstract: Carabrone, a botanical bicyclic sesquiterpenic lactone, has broad-spectrum antifungal activity and is particularly efficient against the devastating phytopathogen Gaeumannomyces graminis var. tritici (Ggt). The antifungal mechanism of carabrone against Ggt, however, remains unclear. The main objective of this study was to investigate the subcellular localization of carabrone in Ggt to gain a better understanding of its mechanism of action. When Ggt was exposed to carabrone (EC value of 28.45 μg/mL) for 7 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…In our previous study, we reported that carabrone exerts significant antifungal activity against G. tritici (Wang et al, 2017b(Wang et al, , 2017c. Using transmission electron microscopy, carabrone was found to have a significant effect on biological oxidation and caused mitochondrial vacuolation in G. tritici.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…In our previous study, we reported that carabrone exerts significant antifungal activity against G. tritici (Wang et al, 2017b(Wang et al, , 2017c. Using transmission electron microscopy, carabrone was found to have a significant effect on biological oxidation and caused mitochondrial vacuolation in G. tritici.…”
Section: Introductionmentioning
confidence: 94%
“…Immunogen (T-BSA) was synthesized according to the method described by Wang et al (2017b) Female BALB/c mice (6 weeks old), purchased from the Xi'an Jiaotong University School of Medicine (Shaanxi, China), were immunized with immunogen (T-BSA). Immunization of the animals and titres of the antisera were monitored by indirect ELISA, as described by Wang et al (2017b). The monoclonal antibody was prepared according to the method described by Wang et al (2017a) with slight modifications.…”
Section: Preparation Of a Monoclonal Antibodymentioning
confidence: 99%
See 3 more Smart Citations